Perfection of labor remuneration in institutions of additional education - Akhmetzhanov, B.; Tazhibekova, K.T.; Shametova , A. (BUKETOV BUSINESS REVIEW, 2018)
The article is devoted to the problem of labor remuneration at the institutions of additional education, which is currently developing in our country. Additional education has a great impact on compulsory education and is aimed at deepening the knowledge and development of students. Today every teacher works in this sphere in addition, paying attention to the extent to which this kind of activity is properly assessed both abroad and in our country and the need to determine the methods of payment for labor from the theoretical aspects that are considered in this article. A comparative analysis of the salaries of employees in the sphere of education of our country with European countries, as well as an analysis of the level of wages of educators with the national wage. The main problem that has arisen in our country is the need for an effective evaluation of the work of the education staff and the introduction of incentive measures. The analysis of the remuneration of teachers working in this organization was conducted and directions for improving the payment of labor were proposed. The proposed methodology for calculating wages will increase the effectiveness of not only the work of institutions of additional education, but also in the whole sphere of education and will be the basis for providing quality services to students.